Spatiotemporal diversity of bacterial endophyte microbiome of mandarin (Citrus reticulata) in the northern Persian Gulf and its HCN production and N2 fixation - Hashemi, Tahereh Sadat; Soltani, Jalal; Samsampour, Davood; Seyahooei, Majeed Askari; Ghasemi, Mostafa (Folia microbiologica, 2025)
Endophytes are symbionts that live in healthy plants and potentially improve the health of plant holobionts. Here, we investigated the bacterial endophyte community of Citrus reticulata grown in the northern Persian Gulf. Bacteria were isolated seasonally from healthy trees (root, stem, bark, trunk, leaf, and crown tissues) in four regions of Hormozgan province (i.e., Ahmadi, Siyahoo, Sikhoran, Roudan), a subtropical hot region in Iran. A total of 742 strains from 17 taxa, 3 phyla, and 5 orders were found, most of which belonged to Actinobacteria (Actinobacteriales) as the dominant group, followed by Firmicutes (Bacillales), Proteobacteria (Sphingomonadales, Rhizobiales), and Cyanobacteria (Synechoccales). The genera included Altererythrobacter, Arthrobacter, Bacillus, Cellulosimicrobium, Curtobacterium, Kocuria, Kytococcus, Methylopila, Mycobacterium, Nocardioides, Okiabacterium, Paracraurococcus, and Psychrobacillus. The most frequently occurring species included Psychrobacillus psychrodurans, Kytococcus schroetri, and Bacillus cereus. In addition, the overall colonization frequency and variability of endophytes were higher on the trunks. The leaves showed the lowest species variability in all sampling periods. The frequency of endophyte colonization was also higher in summer. The Shannon-Wiener (H') and Simpson indices varied with all factors, i.e., region, season, and tissue type, with the maximum in Roudan. Furthermore, 52.9% of the strains were capable of nitrogen fixation, and 70% produced antagonistic hydrogen cyanide (HCN). Thus, C. reticulata harbors a variety of bioactive bacterial endophytes that could be beneficial for host fitness in such harsh environments.
Keywords: Phylogeny; Plant Leaves; RNA, Ribosomal, 16S; Iran; Bacteria; Endophytes; fixace dusíku; roční období; Nitrogen Fixation; RNA ribozomální 16S; Írán; mikrobiota; endofyty; Biodiversity; listy rostlin; Seasons; biodiverzita; Citrus; fylogeneze; Microbiota